Analisa Hubungan Pengelolaan Sampah Terhadap Kejadian Diare di Provinsi Kalimantan Timur - Prajati, Gita; Suhenra Maulana (Journal Serambi Engineering, 2023)
Household waste that unmanaged well can lead into the emergence of infectious diseases, like diarrhea. The waste management level in East Kalimantan province increases every year, directly proportional to cases of diarrhea. This research’s aim is to know the relationship between waste management level and cases of diarrhea in East Kalimantan province. This research using secondary datas analysis as the method. Datas related to waste management and cases of diarrhea are collected from Central Bureau of Statistics of East Kalimantan and National Waste Management Information System of KLHK. There are six districts/cities as the location of collecting the secondary datas, which are Samarinda, Balikpapan, Bontang, Kutai Kertanegara, Paser and Penajam Paser Utara. The datas collected from 2018 to 2022. The data analysis used chi-square. This research shows Paser District has the lowest waste management level among the others. Whereas, Bontang City has the highest waste management level. The Paser District also has the highest cases of diarrhea. The value of asymptotic significance (2sided) from the chi-square test (0.129) lower than 0.05, so it can be concluded that Ho were approved. It implicated that there is no relationship between waste management level to cases of diarrhea in the East Kalimantan province.